Proses Berpikir Siswa dalam Pemecahan Masalah Geometri ditinjau dari Tipe Kepribadian Hippocrates-Galenus - Nilamsari, Dhea Madanti; Fitriyani, Harina (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The purpose of the study was to describe the thinking process of junior high school students in solving mathematical problems in terms of personality types sanguine, choleric, melancholic, and phlegmatic. The thinking process used is based on Piaget's theory which consists of assimilation and accommodation processes. This study used a descriptive qualitative approach and was conducted in one of the state junior high schools in Pangkalpinang. The subjects in this study consisted of 4 students of class VII. Subject selection using the purposive technique. The instruments used were researchers, personality type questionnaires, math problem-solving test questions, and interview guidelines. The validity of the data is done by technical triangulation. Data analysis in this study used the Miles and Huberman model. The results showed that sanguine and phlegmatic subjects carried out assimilation thinking processes at all stages of Polya's problem solving for all types of questions. Choleric subjects and melancholic subjects carried out assimilation thinking processes at all stages of Polya for world problem type questions with abstract context.